Development of the detection direct ELISA kit for carbofuran residue in soil - WU Hui-ming; YANG Ting; ZHU Guo-nian (浙江大学学报. 农业与生命科学版, 2003)
A ELISA kit based on polyclonal antibody was developed to detect the residue of carbofuran in soil. Linear detection of the kits covered a range from 0.01 mg/L to 10.00 mg/L. The mean within-assay、between-assay and total-assay variability were less than 7.72%. The recoveries of carbofuran added to sample ranged from 93.974% to 97.92%. The validity of kit in 4℃ or -20℃ was both above six months.